Beyond the Call of Beauty: Everyday Aesthetic Demands Under Patriarchy. (2nd January 2018) - Archer, Alfred; Ware, Lauren
Abstract: This paper defends two claims. First, we will argue for the existence of aesthetic demands in the realm of everyday aesthetics, and that these demands are not reducible to moral demands. Second, we will argue that we must recognise the limits of these demands in order to combat a widespread form of gendered oppression. The concept of aesthetic supererogation offers a new structural framework to understand both the pernicious nature of this oppression and what may be done to mitigate it.